2022
DOI: 10.1093/rap/rkac021
|View full text |Cite
|
Sign up to set email alerts
|

Using patient-reported data from a smartphone app to capture and characterize real-time patient-reported flares in rheumatoid arthritis

Abstract: Objective To explore the frequency of self-reported flares and their association with preceding symptoms collected through a smartphone app by people with rheumatoid arthritis (RA). Methods We used data from the Remote Monitoring of Rheumatoid Arthritis (REMORA) study, where patients tracked their daily symptoms and weekly flares on an app. We summarised the number of self-reported flare weeks. For each week preceding a flare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…To more comprehensively understand RA disease activity and its manifestations from a patient's perspective, including measure important attributes related to pain and stiffness, it is essential to collect patient reported outcomes (PROs) in addition to physician-derived measures. The addition of remote variables not routinely collected in clinical care allows physicians to better understand what the patient is experiencing including suboptimal treatment response in patients initiating a new medication that may not be feasible with such frequency using current healthcare staff[ 2 , [3] , [4] , [5] ].Recent studies have evaluated the ability of patient-reported outcome measures (PROs) to predict flare in RA patients [ 6 ], measure physical activity as a proxy for disease activity [ 6 ], and study associations between electronic patient-reported outcomes (ePROs) and passive (wearable/actigraphy) data [ 7 ]. These studies also evaluated the ability of RA populations to regularly complete their ePROs and wear their actigraphy devices.…”
Section: Introductionmentioning
confidence: 99%
“…To more comprehensively understand RA disease activity and its manifestations from a patient's perspective, including measure important attributes related to pain and stiffness, it is essential to collect patient reported outcomes (PROs) in addition to physician-derived measures. The addition of remote variables not routinely collected in clinical care allows physicians to better understand what the patient is experiencing including suboptimal treatment response in patients initiating a new medication that may not be feasible with such frequency using current healthcare staff[ 2 , [3] , [4] , [5] ].Recent studies have evaluated the ability of patient-reported outcome measures (PROs) to predict flare in RA patients [ 6 ], measure physical activity as a proxy for disease activity [ 6 ], and study associations between electronic patient-reported outcomes (ePROs) and passive (wearable/actigraphy) data [ 7 ]. These studies also evaluated the ability of RA populations to regularly complete their ePROs and wear their actigraphy devices.…”
Section: Introductionmentioning
confidence: 99%
“…In previous work, we investigated the association between patient-reported flares and daily symptom scores [ 11 ]. The purpose of this analysis was to build on this work by investigating the feasibility of using ML methods to classify self-reported RA flares based on a small data set of daily symptom data collected through a smartphone app.…”
Section: Introductionmentioning
confidence: 99%
“…The benefits of self-management are clear on both the individual and the societal level. RA is a chronic disease with an often-unpredictable course, characterised by intermittent flares and even day-to-day symptom variation [ 11 , 12 ]. Since most patients see their rheumatologist only 3–5 times per year on average [ 13 ], people living with RA should be supported in their ability to manage or react to flares, symptoms or other difficulties they encounter in between clinic visits [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%